Two new endemic species of Monstera (Araceae: Monsteroideae: Monstereae) from Golfito in southern Costa Rica - Cedeño Fonseca, Marco Vinicio (2020)
Monstera croatii M.Cedeño & A.Hay and M. gambensis M.Cedeño & M.A.Blanco (Araceae: Monsteroideae: Monstereae) are newly described and illustrated from cantón Golfito in the Pacific lowlands of southern Costa Rica. Notes are provided on how they can be differentiated from similar species. Monstera croatii is unique in the genus because it reaches its adult vegetative morphology while growing as a terrestrial plant on the forest floor, and climbs only to a very limited height before flowering. Monstera gambensis is one of the smallest species in the genus.